Analisa Stabilitas Lereng Dengan Dinding Penahan Tanah: Studi Kasus: Desa Ciherang Kecamatan Nagreg - Dendi Yogaswara; Agus Deni Komarudin (Jurnal Konstruksi, 2024)
Landslides are a disaster that often occurs in Ciherang Village. The high intensity of rainfall causes unstable slopes resulting in landslides in the Bandung-Garut highway area, Ciherang Village, Nagreg District, Bandung Regency. This area is a mountainous area which has medium to high potential for ground movement to occur. The aim of this research is to determine the stability of slopes using retaining wall reinforcement. Building a retaining wall in the Ciherang village area. One of its functions is to stabilize the land area around the road shoulder so that landslides or land subsidence do not occur due to natural factors (rain or flood) or the pressure factors of the loads acting on it. The method used is a quantitative descriptive method. Descriptive approach with observational data collection techniques in the field for measuring, observing and taking soil samples. A retaining wall is a structure built to support the surface of a slope. Permanent walls are used to withstand lateral pressure from unstable soil due to soil erosion or topographic conditions to overcome soil erosion problems and reduce the risk of road damage. Calculation of soil stress using the Rankine method and stability against failure of soil bearing capacity based on the Terzaghi equation based on characteristic parameters (c and Ã˜). The results of the calculation of the cantilever type retaining wall using soil data from laboratory tests with a retaining wall height of 8 m, base width (L) of 4.80 m, obtained a safety factor against overturning force of 3.2 and a safety factor for shear force of 1.73 . Both safety factors meet the minimum requirement of 1.20.